Meningkatkan Kemampuan Berpikir Kritis Siswa Melalui Model Inkuiri Terbimbing Pada Materi Pengantar Ilmu Geografi - Hamrin; Harizah, Desy Triana Dewi (PT. Pubsains Nur Cendekia, 2023)
The class X-2 students' passivity and dependence on the internet as a source of arguments in discussion sessions during learning result in their critical thinking skills being relatively low. This research aimed to improve student's critical thinking abilities. This type of research was classroom action research and was analyzed using a quantitative descriptive approach with the research subjects of 25 class X-2 students at SMAN 12 Kendari. The results of this research show that the pre-cycle critical thinking ability was obtained with a score of 52 in the low category; in cycle 1, the student's critical thinking ability score was 69 in the sufficient category; and in cycle 2, the score was 81 in the high category. The significant increase from the sufficient category to the high category in the second cycle stage was a result of adjustments (reflection) and continuous teacher improvement in the learning process.